A history of the social struggles in Fatsa 1960-1980 - Morgül, Kerem. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2007., 2007)
This thesis aims to make a modest contribution, via the Fatsa experience, to the efforts to revive the collective memory about the social struggles in Turkey in the 1960s and 1970s. To achieve this target, the thesis utilizes a social history approach that focuses on the everyday experiences of ordinary people regarding social inequalities and their struggles to overcome these inequalities. The social disturbances between 1960 and 1980 are reduced merely to left-right conflicts, youth radicalism and anarchy in the official historiography, and usually to the inevitable social reflections of some macro-structural transformations in the social sciences literature about the period. This thesis argues that in reality these disturbances were a sign of the strict class struggles between laboring masses and capital. In accordance with this argument, it is claimed that the period in question amounted to a historical swelling of the social opposition wave all over the country, as a result of which the resistances and struggles of laboring masses became the principal component of the political sphere that is generally restricted to inter-elite struggles in traditional narratives. Thanks to its local character which ensured that the policies were shaped by a dialectical relation developed between the revolutionaries and the people within the everyday struggles aiming to overcome the concrete problems of the common people, the social opposition in Fatsa acquired an extensive mass support, and this middle-sized coastal town became an arena of one of the most severe social struggles in the country.